Morphometric Analysis and Pattern of Protein and Gene Expression of Apoptosis in Focal Cerebral Ischemia in Rats and the Neuroprotetive Action of Hypothermia and Ketoprofen - Tirapelli, Daniela P. C.; Assis Cirino, Mucio Luiz de; Melo de Carvalho, Camila A.; Novais, Paulo Cezar; Figueredo, Rafael Zimak; Porsani, Lucas Barbosa; Gula, Isabella Stracieri; Rodrigues, Andressa Romualdo; Silva, Jairo Pinheiro da; Pereira, Adriana Lis; Lizarte Neto, Fermino Sanches; Schimming, Bruno Cesar [UNESP]; et al. (Soc Chilena Anatomia, 2020)
This study aimed to investigate the morphometric and the pattern of protein and gene expression related to the extrinsic apoptotic pathway in experimental focal cerebral ischemia and the hole of neuroprotection with hypothermia and ketoprofen. For this analysis, 120 rats were randomly divided into 3 groups (20 animals each): control - no surgery (20 animals); sham - simulation of surgery (20 animals); ischemic - focal ischemia for 1 hour, without reperfusion (80 animals) and divided into four subgroups with 20 animals each: ischemic + intraischemic hypothermia; ischemic + previous intravenous ketoprofen, and ischemic + hypothermia and ketoprofen. The infarct volume was measured using morphometric analysis of infarct areas defined by triphenyl tetrazolium chloride and the patterns of expression of the apoptosis genes (Fas, c-Flip, caspase-8 and caspase-3) and the apoptosis protein caspase-3 were evaluated by quantitative real-time PCR and immunohistochemistry, respectively. Hypo expression of genes of extrinsic pathway of apoptosis was observed: Fas receptor, c-Flip and caspase-8 in the isehemics areas. Increases in the gene and protein caspase-3 in the ischemic areas were also observed, and these increases were reduced by hypothermia and ketoprofen, also noted in the morphometric study. The caspases-3 increase suggests that this gene plays an important role in apoptosis, probably culminating in cell death and that the neuroprotective effect of hypothennia and ketoprofen is involved.
Keywords: Apoptosis; Gene expression; Caspase-3; Cerebral ischemia; Neuroprotection; Hypothermia; Ketoprofen